Adolescent combined hormonal contraceptives and surgical repair of anterior cruciate tears: a risky recommendation based on an unproven causal relationship. Issue 3 (3rd July 2019) - Prior, Jerilynn; Whittaker, Jackie L.; Scott, Alex W.
ABSTRACT: A recent cross-sectional national USA registry of surgery to repair anterior cruciate ligament tears found that fewer adolescent women who reported using combined hormonal contraceptives (CHC) had the surgery. They reviewed a complex literature on ovarian steroidal relationships with connective tissues biology, physiology and clinical issues. They concluded, based on their data and that evidence shows the greatest gender imbalance for women's ACL injury during adolescence, that all adolescent athletic women should be treated with CHC to prevent ACL injury. We caution that this admonition is using association to imply causation, implies we understand the ovarian hormonal relationships with connective tissues while that remains unclear, the directive to use CHC in adolescent ignores the recent meta-analytic evidence that its use is associated with failure to achieve peak bone mass and that these authors have used erroneous inferential reasoning and ignored the other variables besides sex and age related to ACL injury and the convincing evidence that training strategies can prevent tears.